Central pancreatectomy for benign or low-grade malignant pancreatic lesions - A single-center retrospective analysis of 116 cases. Issue 5 (May 2019) - Paiella, Salvatore; De Pastena, Matteo; Faustini, Federico; Landoni, Luca; Pollini, Tommaso; Bonamini, Deborah; Giuliani, Tommaso; Bassi, Claudio; Esposito, Alessandro; Tuveri, Massimiliano; Salvia, Roberto
Abstract: Background: Central pancreatectomy (CP) is a parenchyma-sparing surgery for benign or low-grade malignant pancreatic tumors. This study aimed to evaluate the safety of the procedure and to analyze the long-term pancreatic function. The age-specific incidence ratio (IR) was calculated based on the incidence of diabetes mellitus in the general Italian population of Italy. Materials and methods: Patients submitted to CP from January 1990 to December 2017 at the Department of General and Pancreatic Surgery of the Pancreas Institute of Verona, Italy, were evaluated. Results: The final population was composed of 116 patients. There was a clear prevalence of females (74.1%), the mean age was 48 ± 15 years and the main indication for surgery was a pancreatic neuroendocrine tumor (45.7%). A pancreojejunal anastomosis was performed more frequently than a pancreogastric anastomosis (78.4% vs 11.6%). The mean length of stay was 20 ± 33 days. The overall abdominal complications rate was 62%. The frequency of clinically relevant postoperative pancreatic fistula (grades B and C) was 26.7%. The mortality rate was 0%. The rate of R1-resection was 0.8%, as was the recurrence rate. After a mean follow-up of 12.8 years ±6.5, 6 patients developed new-onset diabetes (NODM, 7.5%), and the IR was 1.36 (95%CI 0.49–2.96). Conclusions: CP is associated with high rates of abdominal complications, however, considering the amount of the normal pancreas that was spared, it might be indicated for selected benign or low-malignancy pancreatic tumors. CP patients have the same incidence of diabetes than the general population.